THE PSYCHOPATHIC BEHAVIOR OF THE ANTAGONIST IN THE NOVEL THE CUCKOOS CALLING BY ROBERT GALBRAITH - Hamzah Rabbani; Agnes Setyowati H; Shita Dewi Ratih P (Universitas Pakuan, 2019)
AbstractThis research discusses the psychopathic behaviour of the antagonist, John Bristow, in the novel The Cuckoo`s Calling by Robert Galbraith. This research aims at identifying the characteristics and causes of psychopathic behavior of the antagonist and the impact on others and himself. The research was conducted using descriptive analysis method and psychoanalysis approach. John, who has hurt others without remorse, is not afraid of repeating his crime. He is able to deceive and manipulate others, not to mention coldhearted, and has a lack of emphaty. Strong id and weak superego originating from John's lack of attention and affection from his parents and closest people are the causes of John`s psychophatic behaviour. John`s psychopathic behaviour in turn causes others to suffer and causes himself to lose his family.Keywords : The Cuckoo`s Calling, Psychopathic Behaviour, Superego, Id, Family.